Cell and Molecular Biology: Concepts and Experiments - Karp Gerald (John Wiley & Sons, 1996)
"...a clear introduction to cell and molecular biology at a relatively affordable price." (Cell Biochemistry & Function, September 2003) --This text refers to an out of print or unavailable edition of this title.